Prasangka Positif Atas Perbedaan Agama dalam Konteks Resolusi Konflik Intergroup Relation Siswa Sekolah Menengah Pertama di Provinsi Aceh - Triyani, Triyani; Karliani, Eli; Saefulloh, Ahmad; Gunawan, Vincentius Abdi (Universitas Negeri Malang, 2022)
The purpose of this study was to analyze the positive prejudice against religious differences in the context of intergroup relation conflict resolution among junior high school students in Aceh Province. This study used a survey method by taking a sample of three schools. The researcher collected the data in State Junior High School 1 Banda Aceh, State Junior High School 2 Banda Aceh, and State Junior High School 19 Banda Aceh. The study results showed that 79 percent of students in problem solving did not look at their religious background, while 21 percent of students solved problems based on their religious background. The prejudice of 70 percent of students about the existence of religion was in a positive category. They tended to give the same treatment to friends with different religious backgrounds in solving a problem.